2014
DOI: 10.1016/j.physrep.2014.03.003
|View full text |Cite
|
Sign up to set email alerts
|

Growth of epitaxial graphene: Theory and experiment

Abstract: A detailed review of the literature for the last 5-10 years on epitaxial growth of graphene is presented. Both experimental and theoretical aspects related to growth on transition metals and on silicon carbide are thoroughly reviewed. Thermodynamic and kinetic aspects of growth on all these materials, where possible, are discussed. To make this text useful for a wider audience, a range of important experimental techniques that have been used over the last decade to grow (e.g. CVD, TPG and segregation) and char… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
203
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 247 publications
(212 citation statements)
references
References 378 publications
3
203
0
2
Order By: Relevance
“…Consequently, graphene domains tend to nucleate in random orientations, producing polycrystalline films. [1][2][3][4][5] Much has been learned about the factors that control domain orientation, particularly on metal substrates. For example, it has been shown that a single, energetically preferred orientation exists on Ir(111), where the preferred graphene orientation is dictated by the amplitude of the moiré corrugation of the graphene film induced by film-substrate interactions.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, graphene domains tend to nucleate in random orientations, producing polycrystalline films. [1][2][3][4][5] Much has been learned about the factors that control domain orientation, particularly on metal substrates. For example, it has been shown that a single, energetically preferred orientation exists on Ir(111), where the preferred graphene orientation is dictated by the amplitude of the moiré corrugation of the graphene film induced by film-substrate interactions.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, the carbon on the surface is formed. Whilst maintaining the relevant parameters of the process, carbon can create the structure of grapheme [14,19]. Another technique for the preparation of graphene on a SiC substrate is the carbon deposition from the gas phase (CVD), so-called vapor phase epitaxy.…”
Section: Growth On Sicmentioning
confidence: 99%
“…This method involves stopping the sublimation by using a suitable flow of argon in the reactor and the deposition of carbon films from a hydrocarbon (eg. propane) added to the carrier gas [19]. The size of thus produced graphene is limited only by the size of the used substrate.…”
Section: Growth On Sicmentioning
confidence: 99%
See 1 more Smart Citation
“…Much interest is directed at the study of proceedings to obtain graphene in the form of highly reduced graphene oxide (rGO) [114,115] or chemically modified graphene [116,117] from the oxidation and exfoliation of graphite and successive chemical reduction. In the bottom-up growth of graphene sheets (Table 1), the synthesis of graphene [70] can be obtained via epitaxial growth [71][72][73], chemical vapor deposition (CVD) [74][75][76][77][78][79][80][81][82], electrochemical reduction of CO and CO 2 [83,84], arc discharge [85,86], unzipping carbon nanotubes [70,87], organic synthesis [88], and pyrolysis [89][90][91].…”
Section: Introductionmentioning
confidence: 99%